Hubungan Perawatan Gigi Dengan Kejadian Karies Gigi di Wilayah Kerja Puskesmas Air Tawar Padang Tahun 2016: Relationship between dental care and the incidence of dental caries in the working area of the Padang Freshwater Health Center in 2016 - Reska Handayani; Mitra Safitri (NERS Jurnal Keperawatan, 2016)
Dental Caries is an infectious diseases that damage tooth structure about 72,1% of Indonesia population in 2007 experienced cavities and motivation to patch the cavities only about 1,6 % and about 46 % of patients have not been handled. The purpose of this research at Puskesmas Air Tawar Padang is too know the relationship of dental care with dental caries event. This research was conducted in January to June 2016. The population in this research was all patient whoo visited the dental pole with a population of 106 people ant this number of sampel 51 people. The sampling technique in this research is accidental sampling. Types of analytical survey research with cross sectional study approach. The adat were analyzed univariate with frequency distribution and bivariate with chi- square statistic test. Data collection trough questionnaires with questionnaires to respondents.The result obtained were suffering dental caries (54,9%) and those who did not dental treatment (51,0%). The result of chi-square test shows that there is a significant correlation (P=0,000) between dental treatment and dental caries occureence in work area of Tawar Puskesmas public halth center in 2016. It is suggested trough the leader of Puskesmas Air Tawar Padamg to increase the action in prevention of dental caries, helath workers in order to improve cooperation in order to control dental caries.